Contrasting Humanitarian and Security Considerations in Refugee Protection in Indonesia: Rohingya Refugees Case Study - Puspasari, Poetika; Handayani, Prawita Meidi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The issue of refugees throughout history, war, and famine has caused population shifts, causing significant displacement and suffering. Today, the number of people has been pushed from their homes hit a record high with the ongoing trend of the world’s conflict. The influx of refugees has created humanitarian and security dilemmas for many countries, including Indonesia. The Indonesian government sees the wave of refugees entering the country as a threat to national security. At the same time, the Indonesian government cannot turn a blind eye for humanitarian reasons. This study analyzes how Indonesia balances humanitarian and security considerations in its efforts to protect refugees. Using a qualitative descriptive method, this study discovers that from Indonesia’s national security point of view, accepting refugees has several political, security, and social-economic consequences; hence, it requires further thorough examinations. Ratifying the 1951 Refugee Convention or its 1967 Protocol with all the following obligations is not the right choice for Indonesia at this time. Refugee issues will also cause immediate effects on the local economy, labor markets, businesses, and social infrastructure, which will cause greater social friction. However, in the name of humanity, Indonesia must continue to support refugee management by maintaining its position as a transit country through better management and a strong legal framework created to this end. This study recommends maximizing Indonesia's role as the Chair of ASEAN and as the former non-permanent member of the UN Security Council to enhance diplomacy and negotiations with Myanmar and the host countries of refugees. Indonesia can strengthen its coastline security and strictly check people entering Indonesia's territory.